2015
DOI: 10.1515/pjap-2015-0036
|View full text |Cite
|
Sign up to set email alerts
|

Marital quality and religiousness of couples parenting children with autism

Abstract: A number of research projects have shown that both religiousness and quality of the marital relationship are important resources that can be used by parents rearing children diagnosed with autism. Our article brings up the link between religiousness of parents who have children with autism and the quality of their marriage. Fifty-three married couples (106 persons) living in Poland and bringing up children diagnosed as having autism were surveyed. Results obtained indicate that there is a relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Examining a sample of Catholics, Noworol and Głaz (2021) showed that religious practices were positively associated with two personality traits: openness and conscientiousness. Religious practices were also positively related to the level of marital satisfaction among Catholic spouses, specifically to intimacy (i.e., a close relationship between spouses), resemblance (expressing harmony between spouses in relation to important goals in family life), and self-realization (perceiving marriage as a relationship that enables each partner to realize themselves) (Gosztyła and Gelleta 2015). As can be seen, religious practices are, therefore, linked to both personal and relational factors.…”
Section: Psychological Measurement Of Religious Practicesmentioning
confidence: 90%
“…Examining a sample of Catholics, Noworol and Głaz (2021) showed that religious practices were positively associated with two personality traits: openness and conscientiousness. Religious practices were also positively related to the level of marital satisfaction among Catholic spouses, specifically to intimacy (i.e., a close relationship between spouses), resemblance (expressing harmony between spouses in relation to important goals in family life), and self-realization (perceiving marriage as a relationship that enables each partner to realize themselves) (Gosztyła and Gelleta 2015). As can be seen, religious practices are, therefore, linked to both personal and relational factors.…”
Section: Psychological Measurement Of Religious Practicesmentioning
confidence: 90%